Comparison of Chemotherapy Regiments between Cisplatin Etoposide and Cisplatin-Docetaxel on 2-Year and Progression-Free Survival in Late-Stage Non-Small Cell Lung Cancer Patients - Salman Paris Harahap; Noorwati Sutandyo; Cleopas Martin Rumende; Hamzah Shatri (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Chemotherapy is one of therapy choices for the advanced Non-Small Cell Lung Cancer (NSCLC). The success in therapy is measured with the 1-year survival, 2-year survival and the Progression Free Survival (PFS). The success is influenced by many factors: resistant to the citostatic, dosage, administer intensity, chemotherapy regiment, type histology, stage, performance status, comorbidity and social economic. In Indonesia, funding and chemotherapy regiment become the challenge for the success of therapy.